Optimization of multiple resources for multi-projects - Aboul Fotouh, Sarah (AUC Knowledge Fountain, 2018)
Optimization of resources is very important in all construction projects. Project managers have to face problems regarding management of cost, time and available resources for single projects. This is more challenging when managing multiple projects. Most of the recent studies focused on optimization of resources for a single project, or a single resource. This thesis presents a numerical model of multiple resources optimization for multiple projects using Genetic Algorithm. Most of the companies in the construction industry optimize the resources for single projects only. However, with the presence of several mega projects in several developing countries running at the same time, there is a need for a model to enhance the efficiency of available resources, and decreases the fluctuation as much as possible and try to maximize the use of the available pool of resources. The proposed model is user friendly, and it can optimize up to nine resources in three different projects running at the same time. The model is used on the identified critical resources. It calculates the cost of each resource, minimize the cost of extra resources as much as possible and generate the schedule of each project within a selected overall program. The model was verified by different scenarios; 1- optimization of multiple resources of a single project; 2- optimization of single resource of multiple projects; 3- optimization of multiple resources of two projects; 4- optimization of multiple resources of three projects meeting deadlines; 5- optimization of multiple resources of three projects but extending the deadlines. The model was able to decrease the extra cost of resources significantly in all scenarios. To validate the model a case study of several residential villas was chosen to test the model on real projects and the extra cost of resources was reduced significantly without extending the projects time.